VILLAGE PHILOSOPHERS’ ROLES IN CREATIVE ENTREPRENEUR : A CASE STUDY OF BAN BATRA COMMUNITY, POMPRAPSATTRUPHAI DISTRICT IN BANGKOK - Pipawakorn, Apichaya; Pooripakdee, Santidhorn (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
In the creative industry of Thailand, there is a cultural heritage that is passed on knowledge from entrepreneurs in the community who have accumulated experience in passing on wisdom from generation to generation. The aim was to study 1) the role of creative community entrepreneurs: a case study of Ban Batra community products 2) A study on the transmission of knowledge about alms in today’s society 3) Propose guidelines for the role of creative community entrepreneurs in ensuring long-term sustainability. The key informants used in the study were 20 people. One community chairperson, two community vice-chairmen, four community committee members, twelve community entrepreneurs, and one village scholar. The research tool was an in-depth interview form. The results of the study found that 1) the issue of the role of creative community entrepreneurs had internal and external factors, 2) the issue of knowledge transfer was found to be transmitted through public relations media both online and offline, and 3) the issue of guidelines for the role of creative community entrepreneurs for social sustainability. It was found that building a network between both the public and private sectors will play an important role in creating sustainability; creating a new generation who will carry on the ancient wisdom of making monk’s alms bowls.